Prevalence of Bovine Tuberculosis in Abattoirs of the Littoral and Western Highland Regions of Cameroon: A Cause for Public Health Concern - J. Awah Ndukum; A. Caleb Kudi; G. Bradley; I. N. Ane-Anyangwe; S. Fon-Tebug; J. Tchoumboue (Veterinary Medicine International)
Bovine tuberculosis (BTB) is widespread but poorly controlled in Africa and M. bovis is posing threats to human health. The risk of cattle handlers to M. bovis prevalence and public health significance of BTB in Cameroon were assessed. Slaughter inspection records from major cities revealed that BTB detection rates in cattle from 0.18% to 4.25% and BTB lesions were most common. Analyses of tissues and sera confirmed BTB in 31% (Ziehl-Neelsen), 51% (culture), and 60% (antibody detection) of test cattle. Among cattle handlers, 81.9% were aware of BTB, 67.9% knew that BTB is zoonotic, and 53.8% knew one mode of transmission but over 27% consumed raw meat and/or drank unpasteurized milk. Respondents who had encountered tuberculosis cases were more informed about zoonotic BTB (P<.05). Tuberculosis is prevalent in cattle destined for human consumption in Cameroon with serious public health implications. Targeted monitoring of infected animal populations and concerted veterinary/medical efforts are essential for control.